AN ANALYSIS OF THE RELATIONSHIP BETWEEN CHRISTIAN FAITH AND MENTAL WELLBEING UTILIZING ITEM RESPONSE THEORY - Yu, Chong Ho (PEOPLE: International Journal of Social Sciences, 2019)
There is a growing concern that more and more American university students suffer from mental distress or disorder. Numerous prior studies have confirmed religious faith and practice to be a promising avenue for alleviating mental problems. Using item response theory (IRT), the current study aimed to verify this assertion with a sample of 436 university students. In this study, the independent variable is faith status/church attendance, which consists of four categories: “I continue to attend church and have faith in Christ,” “I still attend church but have serious doubts of my faith in Christ,” “I have not attended church for over one year but I maintain my faith in Christ,” and “I am not attending church and have abandoned my faith in Christ.” The dependent variable is the IRT’s theta score derived from measures of mental issues in multiple dimensions, including anxiety, depression, loneliness, sadness, suicide attempts, anorexia, etc. For the entire sample, it was found that Christian faith and church attendance must be present together to generate a protective effect against mental distress. Participants who claimed themselves as faithful but did not attend church could not benefit from Christianity as a protective factor. When the sample was divided by gender and race, attending church and keeping faith active still protected students against mental diseases, but the magnitudes varied.